Sugemalimab combined with chemotherapy for the treatment of advanced esophageal squamous cell carcinoma: a cost-effectiveness analysis - Cai, Hongfu; Fang, Ling; Zheng, Zhiwei (Frontiers in Pharmacology, 2024)
Background:This study aims to systematically analyze the cost-effectiveness of the combination therapy comprising sugemalimab and chemotherapy in the management of advanced ESCC from the Chinese healthcare system perspective. Methods: An advanced ESCC patient simulation partitioned survival approach model was developed to mimic the disease progression of patients undergoing treatment with sugemalimab in combination with chemotherapy versus chemotherapy alone. To ensure accuracy and precision, clinical data, treatment costs, and utility values were collected from comprehensive clinical trials and reliable economic databases. The cost-effectiveness analysis was conducted by assessing the incremental cost-effectiveness ratio in relation to the established willingness-to-pay threshold. One-way and probabilistic sensitivity analyses were performed to assess the robustness of the model. Results: The cumulative expenditure for the group of patients administered with sugemalimab amounted to US 41734.87, whereas the placebo group was associated with a total cost of US 22926.25. By evaluating the ICER, which quantifies the additional cost incurred per QALY gained, a value of US 61066.96 per QALY was determined. It is imperative to note that this ICER value surpasses the predetermined threshold for WTP in China, set at US 39,855.79 per QALY. Sensitivity analyses demonstrated that the results were sensitive to the cost of sugemalimab, progression-free survival, and utility values. These fluctuations did not result in a reversal of the study findings. Conclusion: The combination of sugemalimab with chemotherapy for the treatment of ESCC in China is currently not considered a cost-effective therapeutic approach. However, it is suggested that additional reductions in price may facilitate the potential for achieving cost-effectiveness.